PENGEMBANGAN DAN PEMASARAN KOMODITAS KOPI: TRANSFORMASI DARI BUDAYA TRADISIONAL KE BUDAYA PETANI INDUSTRI - Zakki, Muhammad (Jurnal Riset Entrepreneurship, 2020)
Food and Agriculture Organization of United Nation (FAO) 2017 data shows that Indonesia is the fourth largest coffee producing country. In this research, there is a focus on how coffee development and marketing strategies in East Java when viewed from the aspect of farmers cultural transformation and agricultural governance. The research methodology used in this research is observation, in-depth interview discussions with resource persons who are active and representative to be key informants. They were the speakers besides being industry players, farmers and exporters who were members of national and international coffee associations. From the results of the interview with the interviewees, we produce a finding and we do an analysis. The results are as follows: 1) In developing coffee business and marketing it is necessary to do an alternative and strategy that encourages the development of a national coffee business, especially in East Java, by doing; a) Revitalization of plantations; b) Support issues; c) Value added coffee (value added), d) Increased productivity and quality and quality of human resources. 2) The other efforts undertaken in this study are the importance of a transformation value for coffee farming, the transformation which originally adhered to traditionalist culture, namely stagnating to only produce coffee fruit harvest, it needs to be transformed into a modern farmer that is industrial-based agriculture.